Pengembangan Perangkat Pembelajaran Berbasis Diskusi Online Isu Sosiosaintifik Materi Pencemaran Lingkungan di Era Pandemi - Eva Maya Oktaviana; Anif Rizqianti Hariz; Erna Wijayanti; Ismail ismail (Universitas Nahdlatul Ulama Pasuruan, 2021)
This study aims to 1) develop learning tools with self and peer assessment instruments based on an online discussion of socio-scientific issues 2) to determine their effect on students' argumentation skills on environmental pollution material. The development of learning tools uses the 4D development model with the implementation of research only up to 3D, namely the defining, designing, and development stages. The learning tools developed were RPP, LKPD, evaluation instruments, self-assessment instruments,and peer assessment based on Socio-scientific Issues of Environmental Pollution material. The subjects in this study were students from class X MIPA 4 SMA Negeri 5 Semarang for the 2019/2020 school year. The sampling technique used a simple random sampling technique in limited field tests and saturated sampling techniques in operational field tests. The learning tools developed have been validated by expert lecturers and have been revised so that the results are suitable for use. The results showed that the learning tools developed using the pretest and posttest had a